Determination of Oxidized Triacylglycerol Polymers by Preparative Flash Chromatography and High-Performance Size-Exclusion Chromatography - Cao, W.M.; Zhang, K.Y.; Xue, B.; Chen, F.X.; Jin, Q.Z.; Wang, X.G. (Asian Journal of Chemistry, 2013)
Polar compounds were obtained by preparative flash chromatography (PFC). Oxidized triacylglycerol oligomers (TGO), oxidized triacylglycerol dimers (TGD), oxidized triacylglycerol monomers (ox-TGM), diacylglycerols (DG) and free fatty acids in oil were separated through high-performance size-exclusion chromatography (HPSEC). A pool of mixed TGP standard samples was used to check linearity, limit of detection (LOD, S/N ³ 3) and limit of quantification (LOQ, S/N ³ 10). The calibration curves for TGO and TGD were linear in the range of 28-1800 and 11-2800 mg/L with coefficients (r2) greater than 0.99, respectively. The LOD and LOQ were 28 and 1800 mg/L for TGO, 11 and 2800 mg/L for TGD. The LOD is 0.01 % for TGP. The repeatable relative standard deviations (RSDs) of TGP was less than 10 %. Three concentrations of polar compounds-spiked samples were separated by PFC with recoveries ranging from 95.4-97.7 % with RSDs less than 4 %. PFC-HPSEC matched traditional silica column well. TGP determination was completed within 2 h.